(untitled) (American Journal of Islam and Society, 1998)
Dr. Akbar S. Ahmed is probably the most published author in Pakistan. His pub lished works, some of which have earned excellent reviews, make a fonnidable list. As perhaps the best known contemporary Muslim anthropologist, his commitment to the discipline, despite his avocation of being an administrator, is the key to his success. What sets Ahmed apart from most Pakistani authors is that his writings are informed by theoretical considerations and anchored in empirical data. He exudes easy familiarity with methodology, is creative and imaginative in his approach, and can conceptualize. Moreover, he can intellectu.alize problems and issues. As with his earlier writings, his present work is marked by these characteristics. The work is structured around one major theme (Jinnah), and the subthemes of the nature of nationhood, Islam, ethnic and religious identity, the problems of minorities, and the pervasive and ubiquitous influence of media, race, empire, and other factors. Using the methodologies of cultural anthropology, semiotics, and media studies, Ahrned explores old ground with new insights and interpretations. What we have here is neither biography nor history per se; it is part biography, part history of partition, an exploration of Muslim nationhood and Pakistani statehood, and part the Muslim search for identity, a quest that not only inspired the Muslim struggle for Pakistan during the 1940% but which is still relevant (e.g., northern Cyprus, Bosnia, Chechnia, Kashmir, Kosovo, Mindanao [the Philippines], Pattani [Thailand], and even for the Turkish minority in Bulgaria). All said and done, it was the critical problem of identity to which Jinnah addressed himself in the Indian context of the 1930s and 1940s. Thus he represents not only Pakistan, but also a manifestation of the very search for identity in the present larger Muslim world context. His solution to the problems of marginalization, alienation, and even exclusion of Muslims from the corridors of power serves as a beacon to Muslim communities struggling for identity, self-expression, and self-realization. Hence the relevance of Jinnah to the modem Muslim world ...